A method for dyeing cotton fabric with anthocyanin dyes extracted from mulberry (Morus rubra) fruits. (17th March 2016) - Wang, Huayin; Tang, Zhirong; Zhou, Wenlong
Abstract : For the first time, the natural anthocyanin dyes (mainly consisting of cyanidine 3‐glycoside) extracted from mulberry ( Morus rubra ) fruits has been successfully used to dye cotton fabric, with a dyeing property performance good enough for potential commercial applications. In this study, succinic acid was firstly incorporated into cotton fabrics by esterification to the hydroxyl groups of cellulose, forming an anionic site for the dyes. The performance of the modified material was characterised by Fourier transform infrared spectroscopy and tensile strength. Results showed that the tensile strength of cotton fabrics was mostly retained after modification. The anthocyanin extracts from mulberry fruits were used to study the dyeability of the control and modified cotton fabrics. Red and deep purple (aubergine) are two main shades of cotton fabrics dyed with mulberry fruit extracts. Most importantly, aubergine shade is rare in cotton fabrics dyed with natural dyes. Modification with succinic acid clearly increased the colour strength of the dyed cotton fabric. The colour strength of dyed cotton fabric was improved from 2.7 to 5.3 in the case of dyeing without mordants, and from 3.2 to 6.9 in the case of dyeing with tin mordanting. Meanwhile, the colour fastness was improved by 0.5–2 grades with increasing succinic acid concentration in the finish solution. The colour fastness to perspiration, crocking, light, and washing of fabric dyed with simultaneous tin mordanting and modified with 30 g l −1 of succinic acid was found to be acceptable, with a grey scale grade of at least 3. As for home laundering, neutral soapy solution was more acceptable than alkaline soapy solution.